إدارة الوقف الزراعي لمعهد دار السلام كونتور بعقد الإجارة والمزارعة على تحليل سواوت: The Management of Waqf Fields at Pondok Modern Darussalam Gontor (PMDG) Based on Ijarah and Muzara’ah Contract: SWOT Analysis - Mulyono Jamal; Hendri Setiyo Wibowo; Khurun'in Zahro'; Eko Nur Cahyo (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2025)
Efforts to manage agricultural waqf lands are the right step towards increasing the productivity of waqf lands. This study aims to determine the management of the agricultural waqf of the Universitas Darussalam Gontor through lease and sharecropping contracts. This is a qualitative field study conducted at the Universitas Darussalam Gontor, Indonesia. In collecting data, the researcher used observation, interviews, and documents, which were then analyzed using the SWOT approach. The results of this study show that the agricultural endowment management of the Universitas Darussalam Gontor through lease contracts is located in the areas of Fonoroko, Madiun, Kediri, Nganjuk, and Jember, while its management through sharecropping contracts is located in the Mantingan area. The management of agricultural endowments through lease and sharecropping contracts for the Universitas Darussalam Gontor helps the community's economy and welfare because the price of agricultural endowment leases is lower than other agricultural prices.